A Political History of the Valorisation of Cultural Heritage in Italy: Conflicts in a Controversial Social Process - Rech, Giovanna (Italian Sociological Review, 2022)
Valorisation is one of the two functions used by institutions in the transmission of cultural heritage in Italy. While valorisation is a polysemic concept with an uncertain use and wide-ranging implications, the relationships that have been forged between protection, management, realisation, and valorisation are the subject of a controversy that is in conflict with both scholars and the two different aims of social life: social and cultural progress and economic growth. Through a critical approach and from a sociological perspective, this article shows how these two dimensions are in a conflict that touches both the social purposes attributed to cultural heritage and the cultural process through which heritage is produced.